Feed storage practices and aflatoxin contamination of dairy feeds in the Greater Addis Ababa milk shed, Ethiopia - Gizachew, D.; Szonyi, Barbara; Tegegne, Azage; Hanson, Jean; Grace, Delia (International Livestock Research Institute, 2015)
Aflatoxin B1 (AFB1) is a highly toxic metabolite of Aspergillus fungi that contaminates animal feed. A cross-sectional study was conducted at the International Livestock Research Institute (ILRI) in the Greater Addis Ababa milk shed between September 2014 and February 2015. The objectives were to assess the knowledge and practices of dairy value chain actors on aflatoxins, and to analyze feed for the presence of AFB1. A structured questionnaire was administered to value chain actors. A total of 100 dairy farmers, five feed manufacturers, five feed processors and nine feed traders were interviewed and feed samples were collected. All dairy farmers used concentrate feed daily, which commonly included the mixture of wheat bran and noug (Guizotia abyssinica) cake (the byproduct from noug oil factory). In general, feed was stored indoors (94%) in plastic bags. Quality assessment of feed ingredients was limited to visual inspection. Storage time was highly variable and sometimes up to six months long. Preventive measures, such as the practice of keeping feed on raised platforms were not common (15%). Most respondents never heard of aflatoxins (88%). Over 90% of dairy farmers had no knowledge that milk could be contaminated with aflatoxin. We analyzed the level of AFB1 in 114 feed samples from dairy farmers and 42 feed samples from feed producers and processors using enzyme linked immunosorbent assay (ELISA). All the feed samples were contaminated with AFB1 ranging between seven and 419 ppb (ug/kg). Analysis of individual wheat bran and noug cake samples revealed that the contamination level of AFB1 for wheat bran was between nine and 31 ppb while the contamination level for noug cake was between 290 and 397 ppb. Linear regression revealed significant associations between the presence of noug cake in the feed and the levels of contamination of AFB1 in feed. The level of aflatoxin contamination found in feed is alarming and should prompt urgent action to identify suitable interventions. Training should be provided to the dairy sector on risk mitigation strategies. These results suggest that risk mitigation should focus on noug cake to effectively reduce aflatoxin contamination in the peri-urban dairy value chains in Ethiopia.